XENOLITH GARNETS FROM MIR KIMBERLITE PIPE: CHEMICAL COMPOSITION AND EVIDENCE OF METASOMATIC PROCESSES IN THE LITHOSPHERE MANTLE - T. V. Kalashnikova; S. I. Kostrovitsky; K. A. Sinitsyn; E. E. Yudintseva (Геодинамика и тектонофизика)
This paper reports the results on the composition of lithosphere mantle under the Mirny kimberlite field. The authors investigated 57 samples of the mantle xenoliths collected from the Mir pipe. The samples were represented by peridotites (Grt lherzolites) and pyroxenites (Grt websterite, Grt clinopyroxenite and eclogite). The composition of minerals (garnet, clinopyroxene) and various rocks in the lithosphere mantle under the Mirny kimberlite field were analyzed based on petrographic features and chemical data. Besides, PT conditions of rock crystallization were calculated using different geothermobarometers. Garnets from peridotites and websterites show relatively high Mg# (75–83) and low TiO2 contents (up to 0.2 wt. %). Since the eclogite has high-Ca (3.78–9.46 wt. %) and high-Fe (7.77–17.20 wt. %) garnet composition, it lies in the area of wehrlite paragenesis. In general, garnets from the lithosphere mantle under the Mirny kimberlite field have low-Ti garnet composition (up to 0.7 wt. %). Thus, the lithosphere mantle under the Mirny kimberlite field differs from the lithosphere mantle under other diamondiferous fields in a widespread development of eclogite and pyroxenite (up to 50 %), low-Ti composition of rocks, as well as virtual absence of deformed lherzolites. These signs probably indicate minor alteration of silicate metasomatism in the lithospheric mantle under the Mirny field (in contrast to the center of the Siberian craton).